Study of the Compressive Strength of Mortars as a Function of Material Composition, Workability, and Specimen Geometry. (11th February 2020) - Marvila, M. T.; Azevedo, A. R. G.; Alexandre, J.; Vieira, C. M. F.; Zanelato, E. B.; Delaqua, G. C. G.; Xavier, G. C.; Monteiro, S. N.
Abstract : In the present work, the statistical dispersion of the mortar compressive strength as a function of the geometric parameters of the specimens as well as the effect of the mortar workability difference on the compressive strength was investigated. For this purpose, specimens were prepared for six types of mortars: two conventional mortars in the proportions of 1 : 1 : 6 and 1 : 2 : 9 of cement, hydrated lime, and sand, respectively, two with clay replacing lime, and two with marble waste in place of lime. The results confirm the difference between the results found for the two geometries due to the differences in the heights of the molding layers and show that the workability of the mortar modifies the resistance properties, especially in the cylindrical mold where the molding of the specimens is more complex. By comparing the differences between the destructive test results and those defined by the Finite Element Modeling (FEM) for conventional mortars, it was clear that the effect of excess material in the sample during the compression tests did not change the strength properties studied. This facilitates the performance of the assay as specimens may be used excessively on the side without the need for sample rectification.